Anger and the Speed of Full-Body Approach and Avoidance Reactions - Maayan, Iddo; Meiran, Nachshon (Frontiers in Psychology, 2011)
The notion that anger is linked to approach motivation received support from behavioral studies, which measured various motor responses to angering stimuli. However, none of these studies examined full body motions which characterize many if not most everyday instances of anger. The authors incorporate a novel behavioral motor task that tests motivational direction by measuring the reaction times of stepping forward and backward in response to the words "towards" and "away". The results show that, relative to anxiety and control conditions, anger induction resulted in a steeper approach-avoidance RT gradient which was shifted in favor of approach.